دور منصة e-Recours في رقمنة عمليات تسوية طعون حوادث السيارات بين شركات التأمين في الجزائر: The Role of the e-Recours Platform in Digitalizing the Processing of Car Accident Appeals between Insurance Companies in Algeria - كراش حسام (Journal of North African Economies, 2025)
The purpose of this research is to identify the role of e-Recours Platform in digitalizing the processes for treating appeals files of car accident between insurance companies in Algeria. The descriptive method was used to collect and analyze all information related to this platform. We have concluded that the e-Recours platform is the first national digital platform specialized in the electronic processing of these files. The Algerian Unified Office (BUAA) created this platform. From October 01, 2022, the processing of car accident appeals files between 12 insurance companies that underwrite car insurance in Algeria is done through this platform only, starting from sending the appeal file, until the payment of the claim amount and the final closure of this file. In this study, we have mentioned to the most important positives and negatives of the e-Recours platform, and we have suggested some measures that can address these negatives. In general, the existence of this platform in Algeria could pave the way for the development of other projects to digitalize other operations related to the insurance sector in Algeria.